Lokal logistikoptimering för ENA Energi i Enköping - Essendrup, Magnus (2011)
The cost for forestry logistics in Sweden is about 25 percent of the total cost of getting the raw material to industry (Anon., 2010). There might be much to gain by taking a look at your supply chains on the logistic side in your company. In this report the logistic chains by Mellanskog for ENA Energi AB in Enköping has been looked in to. ENA Energis plant is a combined power and heating plant and about 99, 5 percent of their fuel consisted of bio energy in year 2009 (ENA Energi, 2011, länk A). The main purpose with this report is to look at three questions: 1. How does the supply chain look today? From forest to industry. 2. Identify alternative supply chains or optimizations. From forest to industry. 3. Compare the alternatives in question 1 and 2. The report looked into a few different optimizing programs used in forest industry today and what use ENA Energi would have of using these types of programs. ENA Energi uses suppliers for getting the fuel they need, therefore optimization programs might not be applicable for ENA Energi to use. Their business is too small to have an own buy organization. One recommendation is to discuss with their suppliers and require optimizations of their transports in a way that benefits ENA Energi as a company.